Sustainability of TVZ geothermal systems: The regulatory perspective. (January 2016) - Burnell, John; Campen, Bart van; Kortright, Noel; Lawless, Jim; McLeod, Jim; Luketina, Katherine; Robson, Bridget
Highlights: TVZ has 60 years of geothermal development with a focus on sustainable usage. Since 1991 resource allocation & effects management integrated under single RMA-act. Further detailed in regional policies and plans with a focus on resource management. Policies implemented in resource consents & conditions; monitored during operation. Three brief case studies illustrate 3 different 'sustainable modes of operation'. Abstract: Worldwide, the second-longest well-documented history of large-scale use of magmatic-related geothermal systems is in the Taupo Volcanic Zone in New Zealand. Since 1991, geothermal energy usage and its effects have been controlled by a single piece of legislation. This integration of resource allocation and effects management under a single Act, with sustainable management a cornerstone, differs from the approach taken in many countries. The overall objectives are further detailed at a regional level in policies and plans with a focus on resource management. This paper reviews this approach after almost 60 years of development, with the focus on achieving long-term (>100 years) usage including a description of three brief case studies.